Outcomes of Sensitizer-Induced Occupational Asthma: Clinical and Functional Features in Regard to Occupational Exposure After Diagnosis - Minov, Jordan; Stoleski, Sasho; Kocovska-Kamcevska, Nade; Buklioska Ilievska, Daniela; Mijakoski, Dragan; Atanasovska, Aneta; Panajotovic-Radevska, Maja; Bislimovska, Dragana; Zdraveski, David (IJCMCR Open Access, 2025)
Introduction: Outcomes of sensitizer-induced Occupational Asthma (OA) and effectiveness of workplace interventions in regard to occupational exposure after diagnosis still are a matter of discussion. Aim of the study: To evaluate clinical and functional outcomes of sensitizer-induced OA in regard to causative occupational exposure after the diagnosis was established. Methods: We performed a cross-sectional study including 84 patients with sensitizer-induced OA diagnosed in the period 2015-2022. Regarding the workplace intervention after the diagnosis was established, study population was classified as subjects with continued exposure, subjects with reduced exposure and subjects with ended exposure to occupational agent associated with their disease, i.e. subjects removed to another workplace and unemployed subjects. All study subjects ompleted a questionnaire on asthma symptoms and underwent spirometric measurements. Results: Frequency of symptomatic subjects was significantly higher in the group with continued exposure than in the groups with reduced and ceased causative exposure (79.1% vs. 28.6%; P = 0.0001 and 79.1% vs. 38.9%; P = 0.0214, respectively). Frequency of symptomatic subjects in the group of subjects with reduced exposure was non-significantly higher than its frequency in the group of subjects with ceased exposure (38.9% vs. 28.6%; P = 0.4311). Mean value of FEV1 was significantly lower in the groups of subjects with continued and reduced exposure than in the group of subjects with ceased causative exposure (78.4% vs. 85.7%; P = 0.0000 and 80.9% vs. 85.7%; P = 0.0009, respectively). Significant difference was also registered between mean FEV1 value in the group of subjects with continued exposure as compared to its mean value in the group of subjects with reduced exposure (78.4% vs. 80.9%; P = 0.0437). Conclusion: Our findings indicated that cessation and reduction of exposure had better clinical and functional outcomes compared with study subjects with continued exposure. Study subjects with ended exposure had better functional outcomes compared to study subjects with reduced causative occupational exposure.
Keywords: Asthma symptoms; Causative occupational exposure; Continued exposure; Ended exposure; Reduced exposure; Spirometry